Neural network segmentation of images from stained cucurbits leaves with colour symptoms of biotic and abiotic stresses - Gocławski, Jarosław; Sekulska-Nalewajko, Joanna; Kuźniak, Elżbieta (Zielona Góra: Uniwersytet Zielonogórski)
The increased production of Reactive Oxygen Species (ROS) in plant leaf tissues is a hallmark of a plant?s reaction to various environmental stresses. This paper describes an automatic segmentation method for scanned images of cucurbits leaves stained to visualise ROS accumulation sites featured by specific colour hues and intensities. The leaves placed separately in the scanner view field on a colour background are extracted by thresholding in the RGB colour space, then cleaned from petioles to obtain a leaf blade mask.
Keywords: image segmentation; colour space; morphological processing; image thresholding; artificial neural networks; WTA learning; Widrow?Hoff learning; "Cucurbita" species; plant stress; ROS detection